2007
DOI: 10.1109/tifs.2007.897272
|View full text |Cite
|
Sign up to set email alerts
|

A Constructive and Unifying Framework for Zero-Bit Watermarking

Abstract: Abstract-In the watermark detection scenario, also known as zero-bit watermarking, a watermark, carrying no hidden message, is inserted in a piece of content. The watermark detector checks for the presence of this particular weak signal in received contents. The article looks at this problem from a classical detection theory point of view, but with side information enabled at the embedding side. This means that the watermark signal is a function of the host content. Our study is twofold. The first step is to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Last but not least: the higher the 'original' efficiency η(1, 0) = , the less robust is the scheme in the sense that η(γ, σZ )/η(1, 0) = (1 + σ 2 Z ) −η(1,0) decreases faster with the strength of the attack. We have found this feature in other watermarking schemes [7].…”
Section: Fixed Dnr Attackssupporting
confidence: 59%
See 2 more Smart Citations
“…Last but not least: the higher the 'original' efficiency η(1, 0) = , the less robust is the scheme in the sense that η(γ, σZ )/η(1, 0) = (1 + σ 2 Z ) −η(1,0) decreases faster with the strength of the attack. We have found this feature in other watermarking schemes [7].…”
Section: Fixed Dnr Attackssupporting
confidence: 59%
“…One can show [7] that this detection function is centered under hypothesis H0, as required in subsection 2.2, provided E{ w(s) 2 |H0} < +∞. The constant kt enforces that Var{t(r)|H0} = 1:…”
Section: Best Detector For a Given Embeddingmentioning
confidence: 93%
See 1 more Smart Citation
“…This is mostly due to the lack of stationarity and to the wide variety of distribution from a content to another. From the theoretical viewpoint, [8] proposes a unifying theory of zero-bit watermarking, but its main drawback is its lack of universality: the embedder and detector must know the statistical distribution of the host content. More recently, Comesaña et al have found the optimum scheme under the restrictive assumption that the host distribution belongs to the white and Gaussian family [6], whatever its variance.…”
Section: A Contrario Decisionmentioning
confidence: 99%
“…To our knowledge, the majority of the current literature has been focused on watermark detection and many algorithms have been proposed. For instance, in [23] a watermark based on the host content is added and the detection is accomplished with the Neyman-Pearson criterion. In [24], a new perceptual masking is proposed and a correlation based detector is studied for watermark detection.…”
Section: Introductionmentioning
confidence: 99%